1982
DOI: 10.1007/bf01694524
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of selected plasma proteins in hyperdynamic septic shock

Abstract: Abstract. This study was performed on patients (n = 18) suffering from strictly defined hyperdynamic septic shock. Plasma faclors (C-reactive protein, acid al-glycoprotein, fibri nogen, fibrinopeptide A, fibrinogen-fibrin split products, factor XIII, antithrombin III, complement factors C3 and C4, interet-trypsin-inhibitor and CtrmacrogJobulin) measured during hyperdynamic septic shock were highly abnormal. The actjvation and consumption of dotting, fibrinolytic and complement factors due to systemspeeific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
4

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 18 publications
3
16
0
4
Order By: Relevance
“…The LPS-induced consumption of coagulation factors in the present study was similar to that observed in septic patients (2,30). The decrease in plasma Prothrombin and plasma fibrinogen and the increase in soluble fibrin in plasma are evidence of the generation of thrombin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The LPS-induced consumption of coagulation factors in the present study was similar to that observed in septic patients (2,30). The decrease in plasma Prothrombin and plasma fibrinogen and the increase in soluble fibrin in plasma are evidence of the generation of thrombin.…”
Section: Discussionsupporting
confidence: 88%
“…Heparin, the antithrombin III (AT III) cofactor, accelerates the reaction of AT III with thrombin and other clotting factors (29). Thus, the anticoagulant effectiveness of heparin depends on the concentration of AT III in plasma, which is low in cases of septic shock (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a rat model, pretreatment with lipopolysaccharide substantially enhanced the sensitivity to the hypotensive response elicited by systemic administration of PAR-2-activating peptide. 20 Septic patients have a significant elevation in both circulating immunoreactive trypsin and endogenous trypsin inhibitors, 33 and immunoreactive trypsin levels have also been shown to correlate with risk of complications such as adult respiratory distress syndrome. 34 Circulating levels of trypsin are also elevated in the systemic inflammatory response observed in human acute pancreatitis, and both the overall severity of the illness 35 and the development of associated acute lung injury correlate with trypsin activity in a rat model of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Die meisten dieser heute auch für den traumatisch-hämorrhagischen Schock als zutreffend anerkannten Pathomechanismen wurden zunächst sowohl tierexperimentell [224,226,260,261] als auch klinisch [4,37,229,266] …”
Section: Stellenwert Der Bakteriellen Infektion Beim Polytraumaunclassified
“…7 empfindlicher Marker für die akute entzündliche Reaktion bekannt. Dies konnte in klinischen Untersuchungen für septische Verläufe sowie das schwere Gewebetrauma bei großen Operationen und bei Polytrauma bestätigt werden [28,37,48,70,95,231,266]. Dem CRP scheint als Akutphasenprotein eine zentrale Stellung in der unspezifischen Infektabwehr zuzukommen [112].…”
Section: Introductionunclassified